Using 80% trichloroacetic acid in the treatment of ingrown toenails - Hugo Barreiros; Diogo Matos; João Goulão; Pedro Serrano; Alexandre João; Francisco Menezes Brandão (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: Ingrown nails are a very common problem. There are different stages of disease and diverse therapeutic options. Phenol and sodium hydroxide are commonly used agents for chemical matricectomy but both frequently entail excessive healing times. OBJECTIVE: This prospective study aimed mainly to evaluate the efficacy of partial nail avulsion and selective chemical cauterization of the matrix using 80% TCA in the treatment of the ingrowing nail. METHODS: One-hundred-and-thirty-three patients with 197 ingrown toenails were included in this study. Preoperatively, we tried to find predisposing factors to the disease. In the postoperative period, patients were evaluated for potential complications at days 3, 30, 180, 270 and 360. Pain was measured before surgery, as well as 24 hours and 72 hours after surgery. RESULTS: There were only 3 cases (out of 197) of ingrown nail recurrence. Preoperatively, we found the presence of drainage in 82% of patients, which, following the first visit after surgery, was reduced to 19%. Persistent granulation tissue was found in 3% of the patients (versus 75% prior to surgery). The most frequent predisposing factors for the ingrown nail were excessive trimming of the lateral nail plate (63%), plantar hyperhidrosis (58%) and heavy nail folds (39%). Pain was substantially reduced after surgery. CONCLUSION: It is assumed that chemical procedures for the ingrown toenail are associated with delayed healing times but our results demonstrated quick recovery. Using 80% TCA for selective matricectomy in the ingrown toenail is an effective, quick and easy method.